Immunological Changes in Blood of Newborns Exposed to Anti-TNF-α during Pregnancy - Esteve-Solé, Ana; Deyà-Martínez, Àngela; Teixidó, Irene; Ricart, Elena; Gompertz, Macarena; Torradeflot, Maria; de Moner, Noemí; Gonzalez, Europa Azucena; Plaza-Martin, Ana Maria; Yagüe, Jordi; Juan, Manel; Alsina, Laia (Frontiers in Immunology, 2017)
Background: Although anti-TNF-α monoclonal antibodies are considered safe during pregnancy, there are no studies on the development of the exposed-infant immune system. The objective was to study for the first time the impact of throughout pregnancy exposure to anti-TNF-α has an impact in the development of the infant’s immune system, especially B cells and the IL-12/IFN-γ pathway. Methods: Prospective study of infants born to mothers with inflammatory bowel disease treated throughout pregnancy with anti-TNF-α (adalimumab/infliximab). Infants were monitored both clinically and immunologically at birth and at 3, 6, 12, and 18 months. Results: We included 7 patients and 8 healthy controls. Exposed infants had detectable levels of anti-TNF-α until 6 months of age; they presented a more immature B- and helper T-phenotype that normalized within 12 months, with normal immunoglobulin production and vaccine responses. A decreased Treg cell frequency at birth that inversely correlated with mother’s peri-partum anti-TNF-α levels was observed. Also, a decreased response after mycobacterial challenge was noted. Clinically, no serious infections occurred during follow-up. Four of seven had atopia. Conclusions: This study reveals changes in the immune system of infants exposed during pregnancy to anti-TNF-α. We hypothesize that a Treg decrease might facilitate hypersensitivity and that defects in IL-12/IFN-γ pathway might place the infant at risk of intracellular infections. Pediatricians should be aware of these changes. Although new studies are needed to confirm these results, our findings are especially relevant in view of a likely increase in the use of these drugs during pregnancy in the coming years.